Appendicular Diverticulosis - Din, Hafeez-Ud-; Parveen, Bushra (International Journal of Pathology, 2018)
AbstractDiverticulum of the vermiform appendix is an uncommon but interesting problem. The diagnosis is seldom madebefore operation, and the condition may not even be recognized by the surgeon at the time of operation. Righthemicolectomy has sometimes been done because of a mistaken diagnosis of carcinoma. 1Therefore appendiculardiverticulosis mostly comes as a surprise. Appendiceal diverticulum is classified either as congenital or acquiredform like other intestinal diverticulum2.It may be inflamed or not, with or without appendicitis. We report a caseof a 40 year old male who presented with right iliac fossa pain for one day. On the basis of examination and labinvestigation a provisional diagnosis of acute appendicitis was made and appendectomy was performed.Peroperatively a bulbous swelling of the tip of appendix was noticed and carcinoid tumour was suspected.Microscopic examination revealed acute appendicitis as well as two appendicular lumina in the tip of appendix.Both the lumina were bounded by all the four layers of appendix.